PENGARUH PENGAWASAN PIMPINAN TERHADAP DISIPLIN KERJA KARYAWAN PADA PABRIK MESIN INDUSTRI KECAMATAN GEGER KABUPATEN MADIUN - Zhendy Citra Larrynsia Wijanarko (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This study aims to determine Supervision Leadership in Plant Engineering Industry, to know Discipline Employees in Industry Machinery Factory, as well as to determine whether or not Influence Between Monitoring Employee Discipline Leader Against the Machine Factory Geger Madiun County Industrial District. This research uses design conclusive studies. Data collection using questionnaires, observation, documentation and data analysis using linear regression correlation test, F test and t test. The results showed that the supervisory leaders have influence at the same time a positive relationship to discipline employees working at Plant Engineering Geger Madiun County Industrial District. It can be seen from the results of linear regression analysis of Y = 11.277 + 0.840 X. This means that if the leadership supervision increased by 1%, the discipline of employees will increase by 0.840% if other factors held constant. Based on the hypothesis testing results obtained from the correlation test showed that rhitung is 0.6727 while the value rtabel at N = 30 is 0.361. Thus H0 is rejected, meaning that there is difference between the effect of supervision led to the discipline of employees at Plant Engineering Geger Madiun County Industrial District.